Modelling and simulation of microturbine for distribution system network with hybrid filter - Muhammad Shakir, Laili; Zetty Nurazlinda, Zakaria; Nasrul Helmei, Halim; Pungut, Ibrahim (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/